Prevalence of depressive symptoms and associated factors in dental students of a peruvian public university - Petkova-Gueorguieva, Marieta (2015)
Depression, affective disorder of sadness and discouragement with cognitive and behavioral repercussion. The demanding academic environment can trigger depressive symptoms. Objective: The aim of study was to determine the prevalence of depressive symptoms in undergraduated and graduated dental student and factors associated with this. Methodology: Cross-sectional epidemiological design. A stratified random sample of 190 students was selected. To evaluate depressive symptoms was used the abbreviated Spanish version of Zung scale with cutoff 22. Descriptive statistics, bivariate analysis with Chisquare test and multivariate binary logistic regression was applied. Results: 49.5% of dental students had depressive symptoms. The higher rate had female students (60.4% of female students and 37.1% of male OR 2.58 95% CI 1.44 to 4.65). Associated factors with depressive symptoms: dissatisfaction with academic performance (OR 4.59, 95% CI 2.34 to 8.76) and the economic situation (OR 2.69, 95% CI 1.42 to 5.1), heavy academic activity (OR 0.134; IC995% 0.056 to 0.321) and emotional problems (OR 0.282, 95% CI 0.144 to 0.554). Conclusions: Factors associated with depressive symptoms in academic area (dissatisfaction with academic achievement and strong academic load) suggest reviewing aspects of evaluation and academic loads; other associated factors (economic situation and emotional problems) require measures to improve recreation, tutoring, job opportunities and psychological care for students. It is recomended to continue analyzing other factors associated to depressive symptoms in dental students and the instruments measuring depression.